DiOlistic Labeling of Neurons in Tissue Slices: A Qualitative and Quantitative Analysis of Methodological Variations - Staffend, Nancy A.; Meisel, Robert L. (Frontiers in Neuroanatomy, 2011)
Fine neuronal morphology, such as dendritic spines, classically has been studied using the Golgi technique; however, Golgi staining is difficult to combine with other histological techniques. With the increasing popularity of fluorescent imaging, a number of fluorescent dyes have been developed that enable the coupling of multiple fluorescent labels in a single preparation. These fluorescent dyes include the lipophilic dialkylcarbocyanine, DiI; traditionally used for anterograde and retrograde neuronal tracing. More recently, DiI labeling has been used in combination with the Gene Gun for “DiOlisitc” labeling of neurons in slice preparations. DiI sequesters itself within and diffuses laterally along the neuronal membrane, however once the cell is permeablized, the DiI begins to leak from the cell membrane. A DiI derivative, Cell TrackerTM CM-DiI, increases dye stability and labeling half-life in permeablized tissue, however at much greater expense. Here, the DiI and CM-DiI DiOlistic labeling techniques were tested in side-by-side experiments evaluating dye stability and dendritic architecture in medium spiny neurons of the dorsal stratum in both non-permeablized and permeablized tissue sections. In tissue sections that were not permeablized, spine density in DiI labeled sections was higher than in CM-DiI labeling, with the greatest impact on the filapodial spine population. In contrast, tissue sections that were permeablized had higher spine densities in CM-DiI labeled neurons, again largely within in the filapodial spine population. These results suggest that for experiments involving non-permeablized tissue, traditional DiI will suffice, however for experiments involving permeablized tissue CM-DiI provides more consistent data. These data provide the first quantitative analysis of the methodological permutations presented in the literature for neuronal labeling with DiI.